Complex of protection structures on the Shakh River in the Krasnodar Territory - Alexander M. Anokhin; Alexander Yu. Garbuz (Мелиорация и гидротехника)
Purpose: to substantiate a set of measures to ensure reliable protection of the river bank and structures from the impact of water flow and floating objects. Materials and methods. A set of measures to ensure protection of the river bank and structures from the impact of water flow and floating debris is considered. Based on hydrological materials of the river section, a gabion wall is adopted in condition of no overflow. Based on the performed mathematical simulation, a structure of flow redistribution along the width of the river bed towards the deepening of the left river branch in the form of a slot is obtained. Results and discussion. Measures to protect the gabion wall from floating objects using protective structures that allow intercepting large floating tree inclusions and, when filled with floating objects, will divert them to the middle of the river as guide structures, have been developed. The designed composition of structures will ensure safe operation of the adjacent territory and protective structures. Conclusions. Based on the conducted research on the river bank and structures protection from the impact of the water flow, the following measures were proposed: a stepped gabion wall and a wing dam with a slot at the left branch of the river were designed to prevent erosion of the right bank. Mathematical simulation showed that even during a flood, water does not enter the floodplain in the area of the recreational facility, and the flow is redistributed towards the deepening of the left branch. The crest of the gabion wall was designed at an elevation of 81.3 m to protect the floodplain from flooding. It was also proposed to use protective devices from wing dam in the form of a gabion wall, which can be made in the form of a cross-shaped beam or a T-shaped element arranged on a longitudinal beam. The placement of such structures in a flooded area should ensure the capture of all large inclusions of floating trees and their fragments, as well as maintain the free movement of the water flow and the integrity of the gabion bank protection structures.